The mental stress crisis and coping strategies among the first-year female undergraduates at the selected departments of Faculty of Applied Sciences in Sabaragamuwa University of Sri Lanka during the outbreak of Covid-19 - Athukorala, G.V.; Joniton, S. (University of Jaffna, 2022)
With the outbreak of Covid-19, university students had a heightened risk of experiencing mental stress. The study aims to elaborate female students views and their coping strategies with the mental stress status prior, during the outbreak of Covid-19 among the selected first year female undergraduates in Faculty of Applied Sciences, Sabaragamuwa University. The simple random sampling method was utilized and involved 30 number of first year female undergraduates of age between 20- 23 years. A web-based survey was carried out using the google forms, included Depression, Anxiety and Stress Scale (DASS-21). DASS‐21 scoring standard questions have a four point scale system starting from 0 to 3. The level of depression, anxiety, stress, were categorized as normal, mild, moderate, severe, and extremely severe based on the mean scores. Students’ stressors and coping strategies were assessed with open- ended questions. The data were analysed by Microsoft Excel 2013. Among the 30 participants, a total of 100% (n=30) of the undergraduates reported that they were more stressed during the outbreak of Covid-19. Regarding DASS21, 3 (10%), 18 (60%), 4 (13%), 3 (10%), 2 (6%) displayed signs subsequently, normal, mild, moderate, severe, and extremely severe stress conditions. For DASS21, mean scores were calculated for depression, anxiety and stress and had mean scores of 8.1, 5.06 and 9.8 points respectively. The majority of students (76.7%) mentioned “academic pressure” as the primary reason. Among the respondents, only 11 (36.7%) were able to cope with the stress personally. High proportion of respondents indicated experiencing mild to severe levels of stress which alarms to planning prevention programs that are more tailored to the needs of the students and anticipating their needs. It may be possible to increase the number of universities involved in this study and to compare and contrast both gender differences under specific circumstances.
Keywords: COVID-19; University Students; Psychology; Mental Stress; Coping Strategies